Upaya Pendampingan Intensif untuk Meningkatkan Kemampuan Menulis Sesuai Kaidah Bahasa Arab yang Benar di Asrama Darullughah Al Arabiyyah - Basith, Abdul; Badriatul Jamroh, Nurmaya (Keris: Journal of Community Engagement, 2023)
The community service (PkM) that will be carried out will be organized in groups involving several lecturers according to their fields. The target of this program is to provide intensive assistance to improve writing skills according to good and correct Arabic language rules at the Darullughah Al Arabiyyah dormitory and apply it in the simplest form of writing media, namely wall magazines. The objectives of this community service mentoring (PkM) include: (a) Providing Arabic writing training to the mentors in accordance with correct lughawiyah rules (b) Carrying out special mentoring, especially in mastering Arabic writing skills according to correct lughawiyah rules (c ) Increasing the learning motivation of female students to deepen their Arabic writing skills according to correct lughawiyah rules (d) Providing guidance on creating wall magazine concepts at the Darussalam Islamic boarding school using Arabic as well as creating the content. The method uses the ABCD method using a genre process approach in learning writing which is a combination of the process approach and the genre approach. Through the Writing Skills Mentoring activities with an Intensive Program at the Darussalam Islamic Boarding School Blokagung Banyuwangi, changes can be seen that have occurred among the Darullughah al Arabiyyah female students, including: (a) Increasing the quality of the female students' writing (b) Increasing the motivation of the female students to learn Arabic writing (c) Increasing the confidence of the students at the Darullughah Al Arabiyyah dormitory to write Arabic writing in various genres of writing. From the assistance program which was carried out for approximately 3 months from January to March 2023, the assistants can conclude that an intensive Arabic writing assistance program is something that must be implemented, considering that a fun writing program will make students more productive in terms of language.